Trajectories of academic performance over time: differences by social determinants of health and the COVID-19 pandemic - Gresham, Bria; Corcoran, Frederique; Karatekin, Canan (Frontiers in Education, 2023)
We examined (1) differences in academic performance by structural and intermediary determinants of health, (2) associations between duration of college enrollment during the first year of the Coronavirus disease 2019 (COVID-19) pandemic, and (3) their two-way interactions on academic performance using data from two cohorts of freshmen undergraduate students. Participants reported their demographic information, and their structural and intermediary determinants. The university reported academic performance at each semester. Mixed effects models tested repeated measures outcomes (i.e., grade point average (GPA) and courses where the grade received was D, F, Not passing, or Withdrawn (DFNW courses) and generalized linear models tested likelihood of graduation. More unfavorable structural and intermediary determinants were associated with an increased likelihood of receiving a DFNW grade (b = .33 and b = .40, p’s < .05, respectively). Greater unfavorable intermediary determinants were associated with a lower GPA (b = -0.07, p = .159). There were significant interactions between intermediary determinants of health and enrollment duration during COVID-19 for the likelihood of DFNW grades (b = -0.89, p = .008) and graduation (b = 1.31, p = .025), such that Cohort 1 fared worse than Cohort 2. The findings indicate that for those with more unfavorable intermediary determinants, there may have been an initial “shock” of the pandemic that stabilized over time.